Setting targets leads to greater long-term weight losses and ‘unrealistic’ targets increase the effect in a large community-based commercial weight management group - Avery, Amanda; Langley-Evans, Simon C.; Harrington, Michaela; Swift, Judy A. (Wiley, 2016)
Background. Setting personal targets is an important behavioural component in weight management programmes. Normal practice is to encourage ‘realistic’ weight loss but the under-pinning evidence base for this is limited and controversial. This study investigates the effect of number and size of weight loss targets on long-term weight loss in a large community sample of adults. Methods. Weight change, attendance and target weight data for all new UK members, joining January to March 2012 was extracted from a commercial slimming organisation’s electronic database. Results. Of the 35 380 members who had weight data available at 12 months after joining, 69.1% (n=24 447)had a starting BMI≥30kg/m2. Their mean weight loss was 12.9±7.8% and for both sexes, weight loss at 12 months was greater for those who set targets (p<0.001). Those that set ≥ 4 targets achieved the greatest loss (p<0.001). OR for weight loss ≥10% at 12 months was 10.3 (CI 9.7- 11.1, p<0.001) where targets had been set compared to none. At the highest quintile of target size, the size of the first target explained 47.2% (p<0.001) of the variance in weight loss achieved at 12 months. The mean BMI reduction in those with a target >25% was 7.6±4.0 kg/m2. A higher percentage of obese members did not set targets (p<0.001) compared to those with a BMI below 30kg/m2. Conclusions. Much of the variance in achieved weight loss in this population was explained by the number of targets set and the size of the first target. Whilst obese people were less likely to set targets, doing so increased the likelihood of achieving clinically significant weight loss and for some ‘unrealistic’ targets improved results.